Medbh McGuckian's aesthetics of introversion. Issue 4 (2nd April 2020) - Starr, Marlo
ABSTRACT: This article offers a close reading of the poetry of Northern Irish Medbh McGuckian in the context of critical debates about the postcolonial publishing industry. Traditionally, women poets have been excluded from the Irish literary canon, and McGuckian's hermetic poetics in particular have been read as feminist but less concerned with national politics. Exploring McGuckian's composition processes, in which she weaves together quotations from diverse texts, I argue that the poet engages with Troubles history and anticolonial discourses while also undermining gendered national mythologies. I offer the term 'introversion' to describe the ways in which the poet defies London's literary authority in her publishing practices and to consider her opaque poetry's negotiations of market dynamics. I demonstrate that an examination of introverted practices emphasises overlooked issues of gender in attempts to conceptualise a world literary market.